Irrigation Advisory Services: Farmers preferences and willingness to pay for innovation. (September 2021) - Altobelli, Filiberto; Marta, Anna Dalla; Heinen, Marius; Jacobs, Claire; Giampietri, Elisa; Mancini, Marco; Cimino, Orlando; Trestini, Samuele; Kranendonk, Remco; Chanzy, Andre; Debolini, Marta; Courault, Dominique; et al.
Irrigation Advisory Services (IAS) are powerful management instruments aiming to achieve the best efficiency in irrigation water use. So far the literature on farmers' preferences for a specific scheme design of IAS' characteristics and the related willingness to pay (WTP) is scant. This study provides evidence on farmers' preference towards six attributes related to the IAS configuration by using a hypothetical choice experiment. Data were collected from an original survey among 108 farmers from Spain, The Netherlands, Italy, Poland and South Africa. Moreover, we investigated the interplay between these preferences and the individual risk attitude (elicited through a lottery task) as a novel contribution. On average, the results suggest a clear farmers' preference, especially for receiving weather forecasts from the service and for the feature related to water data recording; as the opposite, on average, crop water requirement seems irrelevant. Finally, we found that farmers' WTP for the different IAS services varies across countries and, in some cases, also according to the individual risk attitude.